Interpretation of Multilocular Ameloblastoma and Root Dilation of Teeth - Azda Nurma Himammi; Bambang Tri Hartomo (Perhimpunan Dokter Spesialis Onkologi Radiasi Indonesia (PORI), 2021)
Ameloblastoma is an odontogenic tumor composed of the epithelium of the teeth, and is a benign tumor that develops slowly and does not cause pain. In general, ameloblastoma is benign and clinically ameloblastoma is usually asymptomatic and does not cause changes in sensory nerve function. The indications for periapical radiographs include, among others, to detect apical infection or an inflammation, to know the assessment of periodontal status, to know the presence of trauma to the tooth or to the alveolar bone, to assess the morphology of the tooth root before extraction, during endodontic treatment, to evaluate preoperative and postoperative apical. evaluation of apical cysts and lesions in the alveolar bone and evaluating after implant placement. The radiological features of ameloblastoma that are most often found are multilocular lesions which are often described as soap bubbles if the lesions are large and honeycomb images when the lesions are small, while unicystic ameloblastomas are seen as well-defined lesions surrounded by unerupted dental corona. This radiograph is an important diagnostic support for various types of oral lesions especially those involving the alveolar bone. The diagnosis of ameloblastoma is often made based on radiographs. In this case there was an appearance of ameloblastoma at the tip of the alveolar bone of tooth 18 which is the most common odontogenic jaw tumor, this tumor develops from epithelial tissue and dental tissue in various stages of development.